Getting under the birds’ skin: tissue tropism of Borrelia burgdorferi s.l. in naturally and experimentally infected avian hosts - Norte, Ana Cláudia (2020)
Wild birds are frequently exposed to the zoonotic tick-borne bacteria Borrelia burgdorferi sensu lato (s.l.), and some bird species act as reservoirs for some Borrelia genospecies. Studying the tropism of Borrelia in the host, how it is sequestered in different organs, and whether it is maintained in circulation and/or in the host's skin is important to understand pathogenicity, infectivity to vector ticks and reservoir competency.We evaluated tissue dissemination of Borrelia in blackbirds (Turdus merula) and great tits (Parus major), naturally and experimentally infected with Borrelia genospecies from enzootic foci. We collected both minimally invasive biological samples (feathers, skin biopsies and blood) and skin, joint, brain and visceral tissues from necropsied birds. Infectiousness of the host was evaluated through xenodiagnoses and infection rates in fed and moulted ticks. Skin biopsies were the most reliable method for assessing avian hosts' Borrelia infectiousness, which was supported by the agreement of infection status results obtained from the analysis of chin and lore skin samples from necropsied birds and of their xenodiagnostic ticks, including a significant correlation between the estimated concentration of Borrelia genome copies in the skin and the Borrelia infection rate in the xenodiagnostic ticks. This confirms a dermatropism of Borrelia garinii, B. valaisiana and B. turdi in its avian hosts. However, time elapsed from exposure to Borrelia and interaction between host species and Borrelia genospecies may affect the reliability of skin biopsies. The blood was not useful to assess infectiousness of birds, even during the period of expected maximum spirochetaemia. From the tissues sampled (foot joint, liver, spleen, heart, kidney, gut and brain), Borrelia was detected only in the gut, which could be related with infection mode, genospecies competition, genospecies-specific seasonality and/or excretion processes.